Roles of Golf Biomechanics on Golfer Performance: An Evidence-Based Case Report (Universitas Pendidikan Indonesia, 2025)
Classic and modern swings are movements that are often performed when playing golf with the main difference laid in the position of torso and pelvis. In addition to the swing pattern which already has its own advantages and disadvantages, the same type of swing movement in reality is likely to be executed differently by one golfer to another. The differences in golf swings, biomechanically from address to follow-through, aims to affect the level of performance of a golfer. However, it is necessary to find out biomechanical positions and conditions that have significant influence on golf performance when performing golf swings and shot. This study aimed to determine how the biomechanics of golf swings influence the performance of adult golfers through an evidence-based case report. The search of articles applied a number of inclusion criteria. The articles were searched from Pubmed, Cochrane, Scopus, and manual searches. The result was displayed in the PRISMA Flowchart. Based on the search results, 15 articles were found and met the eligibility criteria. The articles included 1 Systematic Review, 5 experimental studies, and 9 cohorts. The articles show that the angle between thorax and pelvis and the ability to control spinal movement will change the X-factor, while the X-factor stretch affects performance. Weight transfer location, grip position, gender differences, golf functional movement, and skill level also determine performance. X-factor, X-factor stretch, crunch factor, including grip position, and stance are components that can differentiate golfer performance. Understanding the biomechanics factors of an individually-tailored golf swing can help optimize a golfer performance. Further research is expected to include Indonesian golfers, with various handicap levels for the subject criteria, by using various designs, such as RCTs and cohort studies.